Systematic review and meta-analysis of the outcomes following neoadjuvant therapy in upfront resectable gastric cancers compared to surgery alone in phase III randomised controlled trials - Lim Khai Shin, Alva; Ho Si Ying, Adelina; Neo Hui Wen, Sarah; Yeo, Shanwen Charleen; Tay, Kon Voi (Journal of gastrointestinal surgery, 2023)
Background Gastric cancer is the fifth most common malignancy and the fourth most common cause of cancer mortality globally. The role of neoadjuvant chemotherapy in upfront resectable gastric cancer is a subject of ongoing research. In recent meta-analyses, R0 resection rate and superior outcomes were not consistently observed in such regimens. Aim To describe the outcomes following phase III randomised control trials; comparing neoadjuvant therapy followed by surgery against upfront surgery with and without adjuvant therapy in resectable gastric cancers. Methods The Cochrane Library, CINAHL, EMBASE, PubMed, SCOPUS and Web of Science was searched from January 2002 to September 2022. Results 13 studies were included (3280 participants). R0 resection rates were in neoadjuvant therapy arms as compared to adjuvant therapy with odds ratio (OR) 1.55[95% CI: 1.13, 2.13](p=0.007) and compared to surgery alone OR 2.49[95% CI: 1.56, 3.96](p=0.0001). 3-year and 5-year progression-, event- and disease-free survival in neoadjuvant therapy as compared to adjuvant therapy were not significantly increased, 3-year OR 0.87[0.71, 1.07](p=0.19). Meanwhile, comparing neoadjuvant therapy to adjuvant therapy, 3-year overall survival (OS) hazard ratio was 0.88[95% CI: 0.70, 1.11](p=0.71) while 3- and 5-year OS OR was 1.18[95% CI: 0.90, 1.55], p=0.22 and 1.27[95% CI: 0.67, 2.42](p=0.47) respectively. Surgical complications were also more common with neoadjuvant therapy. Conclusion Neoadjuvant therapy yields higher rates of R0 resection. However, improved long-term survival was not seen as compared to adjuvant therapy. Large multi-centred randomised control trials with D2 lymphadenectomy should be performed to better evaluate the treatment modalities.